Direito à moradia: políticas habitacionais em Ananindeua- Pa e o enfrentamento à violência doméstica - LIMA, Ellen Luiza de Oliveira (2021)
RESUMO EM OUTRO IDIOMA OPCIONAL E NÃO REPETITIVO – Inglês: Abstract (dc.description.abstract); Francês: Résumé (dc.description.resume); Espanhol: Resumen (dc.description.resumen); Italiano: Riassunto (dc.description.riassunto); Alemão: Zusammenfassung (dc.description.zusammenfassung); Resumo Indígena (dc.description.indigena). Fonte: PDF This research investigates whether the housing policies adopted in Ananindeua Municipality have acted as an instrument of prevention and / or face domestic and family violence against a woman. Starting from the fundamentality of the premise about the right to housing, provided for in art. XXV of the Universal Declaration of Human Rights and art. 6, composed or roll of social rights, of our Constitution (1988). The first chapter discourse about the establishment process to adequate housing as a fundamental law and seeks to know how this law is being exercised by women in Brazil, especially women in violence situations. It seeks to ascertain which are the main legal institutes that provide or access women to adequate housing at the national level and to understand how they have materialized as ways to combat the violence. The second chapter offer an approach about the discrimination panorama against women and domestic violence. Based on Law 11.340 / 06, the Maria da Penha law, seeks to understand the description of the family violence domestic and comet against women in Brazil and Ananindeua. From this, seeks to analyses the housing’ public politics in Ananindeua and its relationship with the confronting the violence against women, principally in the third chapter. The methodology used will be qualitative, based on bibliographic research carried out both in doctrine, legislation, articles and theses available on the Internet. Will have, with the inductive method for hypothesis application based on data analysis of domestic violence and housing shortage in Ananindeua and interviews with the secretary of the Ananindeua Housing Secretariat and the chairman of the Women's Commission Lawyer of the Ananindeua Subsection. Aimed to identify if these housing policies are being implemented efficiently in the municipality. The research concluded that the precariousness of the right to housing influences the maintenance of situations of violence and housing security, as well as the access to the organs of the women's confrontation network with an important role in gaining the capacity of women in situations of violence.